2023
DOI: 10.1038/s41420-023-01522-x
|View full text |Cite
|
Sign up to set email alerts
|

SCP2 mediates the transport of lipid hydroperoxides to mitochondria in chondrocyte ferroptosis

Abstract: Sterol carrier protein 2 (SCP2) is highly expressed in human osteoarthritis (OA) cartilage, accompanied by ferroptosis hallmarks, especially the accumulation of lipid hydroperoxides (LPO). However, the role of SCP2 in chondrocyte ferroptosis remains unexplored. Here, we identify that SCP2 transports cytoplasmic LPO to mitochondria in RSL3-induced chondrocyte ferroptosis, resulting in mitochondrial membrane damage and release of reactive oxygen species (ROS). The localization of SCP2 on mitochondria is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Mitochondria are the main energy supply organs of ATP. Sterol carrier protein 2-mediated trafficking of peroxidized lipids to mitochondria promotes GPX4 depletion-induced ferroptosis, supporting a role for mitochondria in ferroptosis [ 54 ]. Next, hippocampal tissues from mice were subjected to transmission electron microscopy to elucidate the mitochondrial membrane state after P2RX7 inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are the main energy supply organs of ATP. Sterol carrier protein 2-mediated trafficking of peroxidized lipids to mitochondria promotes GPX4 depletion-induced ferroptosis, supporting a role for mitochondria in ferroptosis [ 54 ]. Next, hippocampal tissues from mice were subjected to transmission electron microscopy to elucidate the mitochondrial membrane state after P2RX7 inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…[58] Another study demonstrated that sterol carrier protein 2 (SCP2) facilitated the transport of cytoplasmic LPO to mitochondria, contributing to the spread of intracellular LPO and accelerating chondrocyte ferroptosis. [59] Bioinformatics analysis and machine learning techniques identified several ferroptosis-related genes involved in OA. The genes ATF3, IL6, CDKN1A, IL1B, EGR1, CD44, AQP8, BRD7, IFNA4, and ARHGEF26-AS1 have been identified as potential target genes for reducing iron overload during OA treatment.…”
Section: Iron Metabolism and Oamentioning
confidence: 99%
“…[ 58 ] Another study demonstrated that sterol carrier protein 2 (SCP2) facilitated the transport of cytoplasmic LPO to mitochondria, contributing to the spread of intracellular LPO and accelerating chondrocyte ferroptosis. [ 59 ]…”
Section: Iron Metabolism and Arthritismentioning
confidence: 99%
See 1 more Smart Citation